[A 35-year-old man with gynaecomastia as the first symptom of hyperthyroidism] - Mullens, A; van den Bruel, A; Vanderschueren, D (2002)
A 35-year-old man suffered painful bilateral gynaecomastia for 2 months due to serious Graves' hyperthyroidism. During treatment with propylthiouracil and levothyroxine, the plasma concentrations of thyroid hormone, sex hormones and sex hormone-binding globulin normalised and the gynaecomastia disappeared. Gynaecomastia occurs in 30 to 40% of men diagnosed with Graves' hyperthyroidism. However, gynaecomastia as a presenting symptom of this autoimmune disease is uncommon.